KEPRIYAYIAN TOKOH DALAM NOVEL WARNA LOKAL JAWA DAN SUMBANGANNYA DALAM PENGEMBANGAN KARAKTER BANGSA - Suroso Suroso (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to describe the upper class characteristics of the characters in novels with the Javanese local color to develop the nation’s character. It employed content analysis using the descriptive-analytic technique. The data sources were novels with the Javanese local color representing certain eras. The findings are as follows. First, people belong to the upper class because of inheritance and hard work. Second, there are two categories of upper class people, i.e. traditional ones with Dutch education and Islamic religion and new ones with university education and professional and structural positions. Third, they have good characters. Fourth, the characters of Javanese upper class people can serve as a basis to build and develop the nation’s character. Fifth, the character development can be carried out in the family by emphasizing religious attitudes and through humanity knowledge development emphasizing interpersonal, emotional, and spiritual aspects.